Baroreflex control of renal sympathetic nerve activity in early heart failure assessed by the sequence method. (7th April 2017) - Lataro, Renata Maria; Silva, Luiz Eduardo Virgilio; Silva, Carlos Alberto Aguiar; Salgado, Helio Cesar; Fazan, Rubens
Abstract : Key points: The integrity of the baroreflex control of sympathetic activity in heart failure (HF) remains under debate. We proposed the use of the sequence method to assess the baroreflex control of renal sympathetic nerve activity (RSNA). The sequence method assesses the spontaneous arterial pressure (AP) fluctuations and their related changes in heart rate (or other efferent responses), providing the sensitivity and the effectiveness of the baroreflex. Effectiveness refers to the fraction of spontaneous AP changes that elicits baroreflex‐mediated variations in the efferent response. Using three different approaches, we showed that the baroreflex sensitivity between AP and RSNA is not altered in early HF rats. However, the sequence method provided evidence that the effectiveness of baroreflex in changing RSNA in response to AP changes is markedly decreased in HF. The results help us better understand the baroreflex control of the sympathetic nerve activity. Abstract: In heart failure (HF), the reflex control of the heart rate is known to be markedly impaired; however, the baroreceptor control of the sympathetic drive remains under debate. Applying the sequence method to a series of arterial pressure (AP) and renal sympathetic nerve activity (RSNA), we demonstrated a clear dysfunction in the baroreflex control of sympathetic activity in rats with early HF. We analysed the baroreflex control of the sympathetic drive using three different approaches: AP vs . RSNA curve, cross‐spectral analysis and sequence method between AP and RSNA. The sequence method also provides the baroreflex effectiveness index (BEI), which represents the percentage of AP ramps that actually produce a reflex response. The methods were applied to control rats and rats with HF induced by myocardial infarction. None of the methods employed to assess the sympathetic baroreflex gain were able to detect any differences between the control and the HF group. However, rats with HF exhibited a lower BEI compared to the controls. Moreover, an optimum delay of 1 beat was observed, i.e. 1 beat is required for the RSNA to respond after AP changing, which corroborates with the findings related to the timing between these two variables. For delay 1, the BEI of the controls was 0.45 ± 0.03, whereas the BEI of rats with HF was 0.29 ± 0.09 ( P  < 0.05). These data demonstrate that while the gain of the baroreflex is not affected in early HF, its effectiveness is markedly decreased. The analysis of the spontaneous changes in AP and RSNA using the sequence method provides novel insights into arterial baroreceptor reflex function. Key points: The integrity of the baroreflex control of sympathetic activity in heart failure (HF) remains under debate. We proposed the use of the sequence method to assess the baroreflex control of renal sympathetic nerve activity (RSNA). The sequence method assesses the spontaneous arterial pressure (AP) fluctuations and their related changes in heart rate (or other efferent responses), providing the sensitivity and the effectiveness of the baroreflex. Effectiveness refers to the fraction of spontaneous AP changes that elicits baroreflex‐mediated variations in the efferent response. Using three different approaches, we showed that the baroreflex sensitivity between AP and RSNA is not altered in early HF rats. However, the sequence method provided evidence that the effectiveness of baroreflex in changing RSNA in response to AP changes is markedly decreased in HF. The results help us better understand the baroreflex control of the sympathetic nerve activity.